Evaluation of Coal Pore Connectivity Using N2 Sorption Isotherm and Spontaneous Imbibition Tests - Tong-qiang Xia; Jiao-fei He; Shi-xing Fan; Qiang-qiang Zhang; Zi-long Li; Dun-shuai Sun (Geofluids)
Pore structure and connectivity of coal are critical factors in coal gas migration and production, which can be characterized by studying the kinetics of capillary imbibition behaviour within the pore spaces. In order to investigate them, six typical coal samples from different collieries in China (Yangcun, Changcun, Gengcun, Yanbei, Dongxia, and Yuwu coal) are selected to carry out N2 sorption isotherm and spontaneous imbibition tests. Results from N2 sorption isotherm tests show that there is a great difference between the total specific surface area and total pore volume among the six coal samples. Their total specific surface area varies from 0.302 to 3.275 m2/g, and the total pore volume varies from 1.782 to 10.94 mm3/g. The pore volume relationship of coal sample among them is in order from the large to small: Dongxia>Yangcun>Gengcun>Yuwu>Changcun>Yanbei coal, and the specific surface area is in order from the large to small: Yangcun>Dongxia>Changcun>Yuwu>Gengcun>Yanbei coal. The imbibition characters of six coal samples were matched using explicit the short-time limit t⟶0 and long-time limit t⟶∞ models by Zhmud et al., respectively. The results show that the long-time limit t⟶∞ model is better. Combined with pore structure analysis, it can be qualitatively analyzed that the imbibition capacity of six coal samples is positively correlated with the connectivity of coal pores, which is ranked as Changcun>Yanbei>Gengcun>Yangcun>Dongxia>Yuwu coal. This work will help understand the mechanism controlling fluid loss and ultimate gas/oil recovery in unconventional hydrocarbon exploration.